Stochastic Contracts and Subjective Evaluations - Matthias Lang (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Subjective evaluations are widely used, but call for different contracts from classical moral-hazard settings. Previous literature shows that contracts require payments to third parties. I show that the (implicit) assumption of deterministic contracts makes payments to third parties necessary. This paper studies incentive contracts with stochastic compensation, like payments in stock options or uncertain arbitration procedures. These contracts incentivize employees without the need for payments to third parties. In addition, stochastic contracts can be more efficient and can make the principal better off compared to deterministic contracts. My results also address the puzzle about the prevalence of labor contracts with stochastic compensation.
Keywords: D80; J33; J41; J70; 330; subjective evaluations; stochastic contracts; stochastic compensation; budget-balanced contracts; moral hazard; subjective performance measures; incentives